(untitled) (Interdisciplinary Studies Journal, 2026)
This study explores the experiences of families who chose to adopt children with disabilities in Brazil—an option that runs counter to a system marked by selectivity and by the ideal of the “perfect child.” Using a qualitative approach and the life-history method, the research involved open interviews with three adoptive families, analyzed through the lenses of Feminist Disability Studies and the Ethics of Care. We sought to understand how these families narrate their decision to adopt, their everyday care practices, and their confrontations with ableism. The narratives reveal care as an ethical and political choice that shifts disability from a category of deficit to one of interdependence. We argue that adopting a child with a disability calls for an ethical reconfiguration of parenthood by unsettling the regimes of normality that sustain traditional expectations of filiation. The study contributes to broadening the debate on inclusion, recognition, and public policies that support adoptive families.